2005
DOI: 10.1161/circulationaha.104.501841
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Syndrome Affects Left Ventricular Diastolic Function

Abstract: Background-The purpose of this study was to determine the role of obstructive sleep apnea syndrome (OSAS) as an independent risk factor for the development of left ventricular diastolic abnormalities. Moreover, we tested the hypothesis that nasal continuous positive airway pressure (nCPAP) improves such alterations in OSAS patients by eliminating apneic events. Methods and Results-In this prospective, randomized, placebo-controlled, double-blind crossover study, 27 consecutive newly diagnosed middle-aged OSAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
223
2
20

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(258 citation statements)
references
References 55 publications
13
223
2
20
Order By: Relevance
“…However, most of them have normal ejection fraction despite signs of the heart failure. 16,17 Previous echocardiographic studies using tissue Doppler imaging and speckle-tracking imaging have demonstrated that OSA subjects may develop subclinical LV systolic and diastolic dysfunction. 1,18,19 Altekin et al 20 have also shown on a smaller group of subjects with OSA, using speckle-tracking echocardiography, that longitudinal and circumferential systolic LV dysfunction is detectable in addition to the diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them have normal ejection fraction despite signs of the heart failure. 16,17 Previous echocardiographic studies using tissue Doppler imaging and speckle-tracking imaging have demonstrated that OSA subjects may develop subclinical LV systolic and diastolic dysfunction. 1,18,19 Altekin et al 20 have also shown on a smaller group of subjects with OSA, using speckle-tracking echocardiography, that longitudinal and circumferential systolic LV dysfunction is detectable in addition to the diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increasing arterial stiffness, obesity is associated with 4‐fold greater prevalence of OSA, which contributes to the pathogenesis of HFpEF through multiple mechanisms: Sympathetic activation increases LV afterload, hypoxic pulmonary vasoconstriction reduces LV preload, oxidative stress stimulates inflammation, and hypoxia predisposes to atrial and ventricular arrhythmias 125, 126, 127, 128, 129…”
Section: Obesity Phenotypementioning
confidence: 99%
“…Independently from hypertension and obesity, OSA impairs LV diastolic function, begets LVH, and thus may hasten HFpEF progression 126, 127, 252, 253, 254, 255, 256, 257, 258. Repetitive sleep arousals and hypoxic episodes heighten sympathetic activity and promote endothelial dysfunction, systemic inflammation, and arterial stiffness that may further increase blood pressure and accelerate atherosclerosis progression 128, 259, 260, 261, 262, 263, 264, 265…”
Section: Comorbid Conditionsmentioning
confidence: 99%
“…1 OSAS also creates right ventricle pressure overload by the mechanical effects of pulmonary obstruction and as such can also affect left ventricular diastolic function. 7,8 We also know from two previous case reports that OSAS may present with recurrent pulmonary oedema. 9,10 In our patient, the first mitral valve reoperation was necessary, due to a demonstrable dysfunction of one of the mitral valve leaflets.…”
mentioning
confidence: 92%
“…7,13,14 In summary, OSAS should be suspected in patients with (recurrent) respiratory insufficiency due to pulmonary oedema, especially if no other causes are found. ■…”
mentioning
confidence: 99%